Deep Untargeted Metabolomics Analysis to Further Characterize the Adaptation Response of Gliricidia sepium (Jacq.) Walp. to Very High Salinity Stress - Braga, Ítalo de Oliveira; Carvalho da Silva, Thalliton Luiz; Belo Silva, Vivianny Nayse; Rodrigues Neto, Jorge Candido; Ribeiro, José Antônio de Aquino; Abdelnur, Patrícia Verardi; de Sousa, Carlos Antônio Ferreira; Souza, Manoel Teixeira (Frontiers in Plant Science, 2022)
The multipurpose tree Gliricidia sepium (Jacq.) Walp. adapts to a very high level of salt stress (≥20 dS m−1) and resumes the production of new leaves around 2 weeks after losing all leaves due to abrupt salinity stress. The integration of metabolome and transcriptome profiles from gliricidia leaves points to a central role of the phenylpropanoid biosynthesis pathway in the short-term response to salinity stress. In this study, a deeper untargeted metabolomics analysis of the leaves and roots of young gliricidia plants was conducted to characterize the mechanism(s) behind this adaptation response. The polar and lipidic fractions from leaf and root samples were extracted and analyzed on a UHPLC.ESI.Q-TOF.HRMS system. Acquired data were analyzed using the XCMS Online, and MetaboAnalyst platforms, via three distinct and complementary strategies. Together, the results obtained first led us to postulate that these plants are salt-excluding plants, which adapted to high salinity stress via two salt-excluding mechanisms, starting in the canopy—severe defoliation—and concluding in the roots—limited entry of Na. Besides that, it was possible to show that the phenylpropanoid biosynthesis pathway plays a role throughout the entire adaptation response, starting in the short term and continuing in the long one. The roots metabolome analysis revealed 11 distinct metabolic pathways affected by salt stress, and the initial analysis of the two most affected ones—steroid biosynthesis and lysine biosynthesis—led us also to postulate that the accumulation of lignin and some phytosterols, as well as lysine biosynthesis—but not degradation, play a role in promoting the adaptation response. However, additional studies are necessary to investigate these hypotheses.